Fostering Intercultural Competence Through AI‑Driven Tools: A Case Study of Linguistic and Cultural Adaptability in Chinese EFL Education - Ma, Guihua; Yang, Xiangjuan (Digital Technologies Research and Applications, 2025)
Intercultural competence has become an essential skill for effective global communication, particularly for English as a Foreign Language (EFL) learners. The integration of artificial intelligence (AI) into educational practices presents significant potential for enhancing both linguistic proficiency and intercultural capabilities. However, there remains a gap in understanding how AI technologies can specifically facilitate the development of intercultural competence among EFL learners. This study adopts a mixed-methods approach to examine the impact of AI technologies on intercultural competence development among 120 Chinese undergraduate EFL students. Quantitative analysis of pre-and post-test data revealed significant improvements in students’ cultural knowledge, attitudinal openness, communication skills, and cultural awareness, with paired t-tests confirming the statistical significance of these gains. Qualitative data, collected through interviews, classroom observations, and platform usage records, further supported these findings, highlighting enhanced emotional engagement, practical application of skills, and immersive learning experiences facilitated by AI tools. The results indicate that integrating AI technologies into language curricula can effectively foster intercultural understanding and communication abilities. This study contributes to the existing literature by providing empirical evidence on the efficacy of AI-based interventions in promoting intercultural competence, offering practical implications for educators and policymakers seeking to leverage AI in language teaching and learning contexts.